Psychosocial Impacts of Unemployment on Young Graduates in Mthatha: An Exploration of External Factors - Kasa, Luvo (Journal of Ecohumanism, 2025)
The rising unemployment rates among youth and graduates in South Africa, as revealed in the 2022 Census report, have significant psychosocial and economic implications. With youth unemployment reaching 55% in 2019 and graduate unemployment increasing from 19.5% in 2018 to 31%, the vulnerability of this demographic is stark. This study explores the psychosocial impact of unemployment on young postgraduates in Mthatha, Eastern Cape. Utilizing a qualitative research design, the study examines themes of self-esteem, social relationships, mental health, and the overall well-being of these individuals. The findings highlight the detrimental effects of unemployment, including reduced self-worth, social isolation, and mental health challenges. The study shows the need for targeted interventions to support young graduates' well-being and employability, address the skills gap, provide mental health support, and enhance job placement services. Without such measures, the long-term consequences of graduate unemployment could exacerbate social exclusion, economic stagnation, and diminished human capital in South Africa.